SISTEM INFORMASI MANAJEMEN KELUHAN PELANGGAN BERBASIS WEB (PT. Semen Baturaja Tbk Palembang) - Akhmad Sayuti (INTECH, 2023)
Customer complaints service is one of the spearheads of increasing customer satisfaction. The intended customer is the employee of the company itself. Coordinated and complete customer complaint handling can provide a positive image of the company / organization. Complete and effective services need to be supported by a coordinated system and cover an entire service cycle that begins with making a complaint, receiving a complaint, updating the complaint status or recapitulation of incoming complaints as a reference for management to assess which domains the customer complains about. This customer complaints management information system is designed to help PT. Semen Baturaja Tbk Palembang to manage and monitor customer complaints. This system focuses on the delivery of complaints from customers based on the type of complaint submitted. Incoming complaints are recorded and then delegated to related parties, as well as monitored the settlement status of the complaint. In this system can also manage customer registrants and company employees to be able to submit complaints and any process in changing the status of complaints or employee data and customer data stored in the report. This system can help management to improve the quality of service, so as to increase customer satisfaction. The method of making the system include system analysis in the form of Flow Chart, system design in the form of Context Diagram, DFD, Use Case Diagram and Activity Diagram The result of the system is applied into web design using PHP programming language and database management using MySQl with Apache web server.